2014
DOI: 10.12738/estp.2014.3.1728
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hearing-Impaired Students’ Requirements for Editing and Revision of Written Texts

Abstract: Writing expression is a transfer of feelings, notions, and experiences of individuals through writing (Kavcar, Oğuzkan, & Sever, 1997; Sever, 2000). During this transfer, it is necessary to specify and arrange the message; select appropriate words; and construct sentences (Göğüş, 1991). Hearing-impaired students have difficulties with context, vocabulary, and spelling rules. They generate short and simply structured sentences, and their sentences may show problems with morphological subject-object agreement (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Program intervensi untuk mendorong keterampilan literasi dini pada tahap ini dapat mengurangi kesenjangan ini. Dengan melakukan pendekatan proses menulis, yang secara umum diakui terdiri dari pramenulis, membuat draf, merevisi dan mengedit, dan menerbitkan, anak-anak dengan gangguan pendengaran meningkatkan keterampilan ekspresi tertulis mereka, mirip dengan anak-anak dengan pendengaran normal (Karasu, 2017).…”
Section: Hasil Analisis Hubungan Antara Early Literacy Skills Dengan ...unclassified
“…Program intervensi untuk mendorong keterampilan literasi dini pada tahap ini dapat mengurangi kesenjangan ini. Dengan melakukan pendekatan proses menulis, yang secara umum diakui terdiri dari pramenulis, membuat draf, merevisi dan mengedit, dan menerbitkan, anak-anak dengan gangguan pendengaran meningkatkan keterampilan ekspresi tertulis mereka, mirip dengan anak-anak dengan pendengaran normal (Karasu, 2017).…”
Section: Hasil Analisis Hubungan Antara Early Literacy Skills Dengan ...unclassified
“…Many studies have been conducted to search for best practices in providing support for hearingimpaired students to write as a potential means of communication at the level of pedagogical practices (e.g., Karasu, 2014;Sirois et al, 2008;Strassman & Schirmer, 2012) and planning (e.g., Sharifi et al, 2016;Sharifi et al, 2017;Xu, 2018). Those studies have indicated urgent steps to take to support hearing-impaired students' writing development, which offers the potentials for their mental and cognitive development and their better quality of life despite some challenges (Sugaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%